Soil organic carbon is not just for soil scientists: measurement recommendations for diverse practitioners. Issue 3 (25th February 2021) - Billings, S. A.; Lajtha, K.; Malhotra, A.; Berhe, A. A.; de Graaff, M.‐A.; Earl, S.; Fraterrigo, J.; Georgiou, K.; Grandy, S.; Hobbie, S. E.; Moore, J. A. M.; Nadelhoffer, K.; et al.
Abstract: Soil organic carbon (SOC) regulates terrestrial ecosystem functioning, provides diverse energy sources for soil microorganisms, governs soil structure, and regulates the availability of organically bound nutrients. Investigators in increasingly diverse disciplines recognize how quantifying SOC attributes can provide insight about ecological states and processes. Today, multiple research networks collect and provide SOC data, and robust, new technologies are available for managing, sharing, and analyzing large data sets. We advocate that the scientific community capitalize on these developments to augment SOC data sets via standardized protocols. We describe why such efforts are important and the breadth of disciplines for which it will be helpful, and outline a tiered approach for standardized sampling of SOC and ancillary variables that ranges from simple to more complex. We target scientists ranging from those with little to no background in soil science to those with more soil‐related expertise, and offer examples of the ways in which the resulting data can be organized, shared, and discoverable.